Antidepressant Use During Acute Inpatient Care Is Associated With an Increased Risk of Psychiatric Rehospitalisation Over a 12-Month Follow-Up After Discharge - Hengartner, Michael P.; Passalacqua, Silvia; Andreae, Andreas; Heinsius, Thomas; Hepp, Urs; Rössler, Wulf; von Wyl, Agnes (Frontiers in Psychiatry, 2019)
Background: Some evidence suggests that antidepressants may relate to poor outcomes in depression. The aim of this study was, therefore, to examine, whether antidepressant use may worsen the long-term outcome in real-world psychiatric patients with both primarily affective and non-affective mental disorders. Methods: Based on a total of n=151 inpatients with a mixed range of diagnoses enrolled at two psychiatric hospitals in Zurich, Switzerland, matched pairs of n=45 antidepressant users and n=45 non-users were selected via nearest neighbour propensity score matching. Pairs were matched according to 14 clinically relevant covariates assessing psychosocial impairments, functioning deficits and illness severity. The two outcomes of interest were the number and total duration of all rehospitalisations over a 12-month follow-up after discharge from the hospital based on the official clinical registry. Results: Altogether 35.6% of antidepressant users were rehospitalized at least once, as compared to 22.2% in matched non-users. Two or more rehospitalizations occurred in 22.2% of antidepressant users but only in 2.2% of non-users. In antidepressant users, the mean total duration of rehospitalisations was 22.22 days, as compared to 8.51 in matched non-users. According to Poisson regression analyses, antidepressant use during acute inpatient care prospectively relates to both a higher risk (incidence rate ratio [IRR]=3.64, 95% confidence interval [95%-CI]=1.71-7.75, p=0.001) and a longer duration (IRR=2.61, 95%-CI=1.01-6.79, p=0.049) of subsequent rehospitalisations. These findings were consistently replicated when traditional multivariable regression analysis was applied to the full sample. Findings also replicated when patients with affective and non-affective disorders were analysed separately. Conclusions: Our findings raise the possibility that, in the long-term, antidepressants may impair recovery and increase the risk of rehospitalisation in patients with both primarily affective and non-affective disorders. More work is required to explore possible aetiopathological pathways leading to psychiatric rehospitalisation.